Serum IgG2 levels predict long-term protection following pneumococcal vaccination in systemic lupus erythematosus (SLE). Issue 44 (14th October 2020) - Gerard, Anne-Laure; Goulenok, Tiphaine; Bahuaud, Mathilde; Francois, Chrystelle; Aucouturier, Pierre; Moins-Teisserenc, Helene; Batteux, Frédéric; Papo, Thomas; Sacre, Karim
Highlights: SLE patients are highly susceptible to pneumococcal infection. >50% of SLE patients fail to reach immune protection after pneumococcal vaccination. IgG2 serum level before vaccination is strongly indicative of long-term protection. Abstract: Systemic lupus erythematosus (SLE) patients are at risk for pneumococcal infection. Twenty-one consecutive SLE patients (40[25–75] years) received the sequential PCV13/PPSV23 vaccine and factors associated with long-term protection were analyzed. Immune protection, defined by an antigen-specific IgG concentration ≥1.3 µg/mL for at least 70% of 7 pneumococcal serotypes was assessed at baseline, 2, 6, 12 and 36 months defining long-term protection. Only 10 patients showed pneumococcal immune protection 36 months after vaccination. Eleven (52.4%) patients had no long-term protection with a seroconversion that never or only transiently occurred. SLE disease features, treatment received and immunological characteristics did not differ between protected and unprotected patients except for the pre-vaccination IgG2 serum levels. Serum IgG2 level >2.125 µg/ml showed a sensitivity of 100% and a specificity of 90.9% for long-term protection. Sequential pneumococcal vaccination conferred poor immune protection in SLE. Baseline IgG2 serum level identified patients able to benefit from pneumococcal vaccination.